The Synthesis of MnFe2O4-Activated Carbon Composite for Removal of Methyl Red From Aqueous Solution - Fahma Riyanti; Poedji Loekitowati Hariani; Widia Purwaningrum; Elfita Elfita; Shella Santika Damarril; Iqlima Amelia (Universitas Jenderal Soedirman, 2018)
In this study, MnFe2O4-activated carbon composite was synthesized by co-precipitation method and applied to adsorb methyl red dye. MnFe2O4-activated carbon composite was made with the mass ratio of activated carbon and MnFe2O4 of 1:2. The composite characterization by using X-Ray Diffraction, Fourier Transform Infrared Spectroscopy, Scanning Electron Micrograph, and Energy-Dispersive X-Ray Spectroscopy, the surface area using the Brunauer, Emmett and Teller and magnetic properties by using Vibrating Sample Magnetometer. The adsorption parameters include contact time, and adsorbent weight. The spectra of FTIR MnFe2O4-activated carbon composite analysis show the presence of Fe-O and Mn-O which is not present in the spectra of activated carbon. SEM analysis shows that the composite has pores and MnFe2O4 oxides are spread on its surface. The composition of the composite consists of C, O, Fe, and Mn. The composite has a surface area of 143.992 smaller than that of the activated carbon of 217.697 m2/g. However, the composite has magnetic properties with the saturatization magnetization of 17.91 emu/g. The optimum condition of the composite for adsorption of methyl red was obtained at a weight of 0.15 g, and contact time of 100 minutes. The adsorption of the composite was in accordance by pseudo-second-order kinetic and Langmuir isotherms with adsorption capacity of 81.97 mg/g.